Influence of NH 4 Br as an ionic source on the structural/electrical properties of dextran-based biopolymer electrolytes and EDLC application - Hamsan, M.H. (Springer, 2020)
Biopolymer electrolytes (BPEs), consisting of ammonium bromide (NH 4Br) as the ionic provider and dextran (Leuconostoc mesenteroides) as the polymer host, are prepared by the solution cast technique. Interactions of cations from the salt have been confirmed with hydroxyl (OH) and glycosidic linkage (CâOâC) groups of dextran via Fourier transform infrared analysis. Electrolyte with 20Â wt NH 4Br maximized the ionic conductivity up to (1.67 Â± 0.36) Ã 10 - 6Â SÂ cm - 1. The trend of conductivity has been verified by field emission scanning electron microscopy, where the electrolyte surface became rough as the concentration of NH 4Br exceeded 20Â wt. The contribution of ions as the main charge carrier in the BPE is confirmed by transference number analysis as tion= 0.92 and te= 0.08. From linear sweep voltammetry, it is found that the highest conducting BPE in this work is electrochemically stable from 0 to 1.62Â V. The fabricated electrochemical double-layer capacitor (EDLC) has been tested for 100 chargeâdischarge cycles and verified by cyclic voltammetry. Â© 2019, Indian Academy of Sciences.